(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Cloud storage in public systems has become a major issue to control data access. A pliable and most secure way to secure the data in the cloud severs for cloud storage is by using Ciphertext-Policy Attribute-Based Encryption (CP-ABE). But, in existing scheme the secure key distribution and verification is done by a single attribute authority which take a lot of time. When it is done by the single attribute authority, it is like a single-point play acquired in a big cloud storage system. There will be users who will be waiting for secret keys for a long-time which result in the less efficiency of the system. Many solutions have been proposed like multi authority scheme to overcome this problem but was unable to overcome this problem. Therefore, this articleproposed a data confidentiality against an adversary which knows the encryption key and has access to a large fraction of the ciphertext blocks. To this end, we propose Bastion, a novel and efficient scheme that guarantees data confidentiality even if the encryption key is leaked and the adversary has access to almost all ciphertext blocks. We analyze the security of Bastion, and we evaluate its performance by means of a prototype implementation. We also discuss practical insights with respect to the integration of Bastion in commercial dispersed storage systems. Our evaluation results suggest that Bastion is well-suited for integration in existing systems since it incurs less than 5% overhead compared to existing semantically secure encryption modes.